Cover Feature: Coherent Evolution of Signal Amplification by Reversible Exchange in Two Alternating Fields (alt‐SABRE) (ChemPhysChem 23/2021). Issue 23 (3rd December 2021) - Pravdivtsev, Andrey N.; Kempf, Nicolas; Plaumann, Markus; Bernarding, Johannes; Scheffler, Klaus; Hövener, Jan‐Bernd; Buckenmaier, Kai
Abstract : The Cover Feature illustrates the quest for efficient Signal Amplification By Reversible Exchange (SABRE). It shows conventional SABRE on the left side and the method alt‐SABRE on the right side, where the polarization evolution switches back and forth between the strong coupling regime at ∼1 mT and the weak coupling regime at ∼50 mT. With this effect the polarization of 15 N can be boosted by at least 30%. The authors thank the DEAL project for promoting open access to research publications. More information can be found in the Communication by Andrey N. Pravdivtsev, Kai Buckenmaier and co‐workers .